Electronic emission of radio-sensitizing gold nanoparticles under X-ray irradiation: experiment and simulations - Casta, R.; Champeaux, J.-P.; Sence, M.; Moretto-Capelle, P.; Cafarelli, P.; Amsellem, A.; Sicard-Roselli, C. (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2014)
In this paper, we present new results on electronic emission of Gold Nanoparticles (GNPs) using X-ray photoelectron spectroscopy (XPS) and compare them to the gold bulk electron emission. This subject has undergone new interest within the perspective of using GNPs as a radiotherapy enhancer. The experimental results were simulated using various models (Livermore and PENELOPE) of the Geant4 simulation toolkit dedicated to the calculation of the transportation of particles through the matter. Our results show that the GNPs coating is a key parameter to correctly construe the experimental GNPs electronic emission after X-ray irradiation and point out some limitations of the PENELOPE model. Using XPS spectra and Geant4 Livermore simulations, we propose a method to determine precisely the coating surface density of the GNPs. We also show that the expected intrinsic nano-scale electronic emission enhancement effect—suspected to contribute to the GNPs radio-sensitizing properties—participates at most for a few percent of the global electronic emission spectra of the GNPs compared to gold bulk.